1996
DOI: 10.1038/382158a0
|View full text |Cite
|
Sign up to set email alerts
|

A PET study of the neural systems of stuttering

Abstract: The cause of stuttering is unknown. Failure to develop left-hemispheric dominance for speech is a long-standing theory although others implicated the motor system more broadly, often postulating hyperactivity of the right (language nondominant) cerebral hemisphere. As knowledge of motor circuitry has advanced, theories of stuttering have become more anatomically specific, postulating hyperactivity of premotor cortex, either directly or through connectivity with the thalamus and basal ganglia. Alternative theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
293
6
10

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 403 publications
(345 citation statements)
references
References 22 publications
36
293
6
10
Order By: Relevance
“…First, previous research identified the overactivation of the right cerebellum as a neural signature of stuttering (Brown et al, 2005) and as specific to stuttered speech (Braun et al, 1997;Fox et al, 1996). Although the participants in this study produced fluent speech during the experiment, we also found overactivation in the right cerebllum.…”
Section: The Neural Substrates For Atypical Execution Process In Stutcontrasting
confidence: 39%
See 1 more Smart Citation
“…First, previous research identified the overactivation of the right cerebellum as a neural signature of stuttering (Brown et al, 2005) and as specific to stuttered speech (Braun et al, 1997;Fox et al, 1996). Although the participants in this study produced fluent speech during the experiment, we also found overactivation in the right cerebllum.…”
Section: The Neural Substrates For Atypical Execution Process In Stutcontrasting
confidence: 39%
“…Correspondingly, we also found an additional backprojection from the left PMA to the right cerebellum among stuttering speakers, which was absent among non-stuttering controls. This backprojection may be closely related to the widely reported overactivation of the right cerebellum in stuttering speakers (e.g., Braun et al, 1997;Fox et al, 1996;Ingham et al, 2000). The alteration in the cerebellum-PMA circuit indicates that when producting rapid rhythmic speech, the motor cortex of stuttering speakers may be out-ofcontrol even when the linguistic plan is intact.…”
Section: The Neural Substrates For Atypical Execution Process In Stutmentioning
confidence: 80%
“…Problems with the auditory cortex and vocal feedback processing have been suggested to underlie stuttering in some patients (Timmons and Boudreau, 1972;Fox et al, 1996). In particular, masking noise has been shown to reduce stuttering (Maraist and Hutton, 1957), possibly due to the blockade of vocal feedback during speech.…”
Section: Further Implications For Vocal Feedback Monitoringmentioning
confidence: 99%
“…Yet while considerable progress has been made towards identifying regions of the cerebral cortex involved in speech motor control [43,60,88], there is a paucity of details concerning how sensory cues are physiologically integrated into the vocal motor pathways within the cortex. There are some significant differences in brain architecture and activity patterns between stutterers and non-stutterers, particularly in speech and language sensorimotor regions of the cortex [31,32,55], but whether or not these large scale differences ultimately unmask greater insight into sensory feedback control of speech remains to be seen.…”
Section: The Significance Of Behavioral Context In Audio-vocal Integrmentioning
confidence: 99%